Para além dos sonhos de Jaquet-Droz: o direito e as relações entre humanos e máquinas - Bachmann, Mickhael Erik Alexander (Universidade do Vale do Rio dos Sinos, 2018)
This research aims to verify the impact of human-machine relations in Law. Therefore, the work begins with a brief history of artificial intelligence, followed by the presentation of a contemporary case of an android with citizenship and a possible hypothetical case that does not yet exist but does not seem to be impossible. Both examples will serve to illustrate much of the discussions that will follow in the next chapters. Once the prolegomena are presented, the concept of 'singularity' along with the utilitarianism of preferences - a system of normative ethics that will be used to respond to the emerging problems of the post-human world - will be stated. Two essential arguments for the work will also be pointed out: (i) the marginal cases argument and (ii) the argument of equal consideration of moral interests, and both will be exposed according Peter Singer’s work. Next, Peter Carruther’s and Richard Posner’s critics to Singer’s thought will be exposed and Singer’s arguments will be applied to post human world. Once the impacts of Singer’s arguments in the proposed scenario are understood, it will be sought to identify how to solve the relational problem between humans and machines. Thus, an analysis of some fundamental legal terms, such as 'person' and 'personality' and, in identifying the difficulty of properly defining such words without also including robots, it is pretended to conceptualize 'robots' to see if it is possible to identify some necessary condition capable of differentiating humans from machines in some relevant aspect. In such attempt a great conceptual difficult can be verified, since it doesn’t seem to exist a clear enough concept that doesn’t lead to other unwelcome scenarios. Then the data of a research conducted in European Union will be exposed to examine what humans think of artificial intelligence and robotics – the single research about this subject found with rigorous data collection and methodology – aiming to perceive which are the greatest population worries. The study finishes with a proposal based on Sam Harris’ Moral Landscape, which indicates that there is something objective about morals and at least it is no need to show concern with a completely relativist scenario. However, it was not possible at the present time to identify a way of giving Law a guide to rule the relations between humans and machines - at least it was not possible through the utilitarianism of preferences and the arguments presented in this work.
Keywords: Direito; Pós-humanismo; Singularidade; Ética; Utilitarismo de preferências; Law; Post-humanism; Singularity; Ethic; Preference utilitarianism; ACCNPQ::Ciências Sociais Aplicadas::Direito